Holocene paleoreconstruction of the southwestern Atlantic ocean: a multiproxy approach of the paleoclimatic, paleoceanography and paleotemperature variability - Santos, Felipe Rodrigues dos (2024)
The Holocene period exhibited crucial climatic features that facilitated the expansion and advancement of human civilization. Many siliciclastic continental margins have specific bathymetric and depositional characteristics that cause the formation of mud deposits that provide sedimentary records capable of recording climatic and oceanographic variations over geological periods. An understanding of the mechanisms behind climate fluctuations and the identification of cyclical events in the geological archives from this era can provide insights into the sensitivity, frequency, and likelihood of future climate change at local, regional, and global scales. To study the paleoenvironmental variations in the southern Brazilian continental shelf, two high-resolution sediment records (#557: 33.79°S - 52.21°W 61m depth, #561: 33.27°S - 51.3°W 90 m depth) were used in association with sedimentological, elemental, isotopic and molecular proxies (grain-size, total organic carbon, δ13C, n-alkanes, alkenones, and δ13C-alkanes) to reconstruct the paleoclimate, paleoceanography, and paleotemperature variations throughout the Holocene, understanding the respective forcing mechanisms that has triggered SST variations in the Southwestern Atlantic Ocean (Chapter 2) as well as the input, transport, and deposition dynamic of terrigenous material, shifts in vegetation, and variations in hydrological patterns (Chapter 3). The SST-UK37 variations in our records can be attributed to the interaction between the warm, salty, and nutrient-poor Subtropical Surface Water (STSW) and the cold, fresh, and nutrient-rich Subantarctic Surface Water (SASW). In the early Holocene, the rise in relative sea level (RSL) and the movement of the northern boundary of the subtropical westerly winds (SWW) were the primary factors influencing the latitudinal variation of the Subtropical Shelf Front (STSF). Once the relative sea level (RSL) stabilized around 5000 cal BP, the northward movement of the Plata Plume Water (PPW) became a noticeable characteristic of sedimentation and circulation in the inner shelf of southeast South America. This movement directly affected the dynamics of ΣC37Alk and SST-UK37. The RSL rise in the early Holocene is also the primary factor influencing the sedimentary organic matter. This is accompanied by a notably weaker South American Monsoon System (SAMS) and reduced precipitation over the La Plata River (LPR) region, with the terrigenous organic material in this period originating from both the LPR and small rivers from the neighboring continent. During the mid-Holocene, a higher RSL caused a trapping of sediments LPR estuary resulting in a low accumulation of terrigenous material in the southern Brazilian shelf. From 6000 cal yrs BP, a shift in the local origin of terrigenous organic matter coincides with a decrease in RSL and an influence of Plata Plume Water (PPW) in the region. During the late Holocene, with a stabilized RSL, the highest levels of southern summer insolation occurred, an increase in the South American Monsoon System (SAMS) and the establishment of El Niño-Southern Oscillation (ENSO), a greater rainfall regime was established in southeastern South America, noticeable at 4000 cal yrs BP and intensified after 2000 cal yrs BP.